1985
DOI: 10.1002/hep.1840050504
|View full text |Cite
|
Sign up to set email alerts
|

Drug–Induced Hepatitis Associated With Anticytoplasmic Organelle Autoantibodies

Abstract: A study from five hepatology units documenting 157 cases of drug-induced hepatitis and a second study from a laboratory of immunology which tested more than 100,000 sera permitted us to establish the frequency of antiorganelle antibodies and their diagnostic value in drug-induced hepatitis. In drug-induced hepatitis caused by a heterogenous group of drugs consisting of ajmaline, aminopterine, isaxonine, isoniazid, perhexiline, phenylbutazone and troleandromycine, antiorganelle antibodies were absent or rare. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…1 could be quite general in immunoallergic drug-induced hepatitis. 2. The evidence that P-450pA (described in reference 19 and used in this paper), the phenacetin O-deethylase, is the human P-4501A2 gene product may be summarized as follows.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…1 could be quite general in immunoallergic drug-induced hepatitis. 2. The evidence that P-450pA (described in reference 19 and used in this paper), the phenacetin O-deethylase, is the human P-4501A2 gene product may be summarized as follows.…”
Section: Introductionmentioning
confidence: 94%
“…Anti-LKMl antibodies were also found in children with an idiopathic type of chronic active hepatitis where a drug could not be identified in the etiology of the disease (1,2,3). The microsomal drug-metabolizing enzymes, P-45011D6 (for anti-LKM 1), P-4501IC8/ 9/10 (for anti-LKM2), trifluoroacetylated carboxylesterase, or several unidentified microsomal proteins (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) were found to be recognized by the various autoantibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Some drugs have been found to induce immunoallergic hepatitis in humans as well as the appearance, in human serum, of circulating antibodies that are directed against cell organelles (1,2). By using immunofluorescence techniques, it was shown that some of these antibodies specifically recognized as yet unidentified macromolecules of the endoplasmic reticulum of rat liver or kidney cells (3).…”
mentioning
confidence: 99%
“…Transiently detectable serum antimitochondrial antibodies have also been reported in subjects with liver damage presumably induced by Teucrium chamaedrys (germander) [8] and an anticonvulsant [9]. In addition, antibodies against various cytosolic organelles, including mitochondria, have been reported in hepatitis induced by a variety of other drugs [10].…”
Section: Discussionmentioning
confidence: 99%